At the Sources of the Twentieth-Century Analytical Movement : Kazimierz Twardowski and His Position in European Philosophy - Jadacki, Jacek,; Brożek, Anna, (Poznań Studies in the Philosophy of the Sciences and the Humanities ;, 2022)
The volume contains works showing the comprehensive contribution of Kazimierz Twardowski, the founder of the Lvov-Warsaw School, to the European analytical movement. The readers of the volume will learn, among other things, how the theoretically fertile distinction between act and product introduced by Twardowski turned out to be. Furthermore, this volume illustrates the importance of Twardowski's defense of alethic absolutism. Finally, readers will learn about the conceptual tools developed by Twardowski, enabling the explanation of the phenomenon of still lingering prejudices, as well as Twardowski's conception of rationality, and about his attitude towards formal and informal logic as well as logical education. An undoubted novelty of the volume is that it provides a kind of parametrization of Twardowski's continuously increasing position in global philosophy by referring to the complete bibliography of works by and on Twardowski in European languages (other than his native language) up until 2020.